The Effect of Workforce Diversity on Employee Job Satisfaction - Nurwisesa, Nurwisesa; Andhika, Muhammad (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to determine the effect of workforce diversity on employee job satisfaction in South Tangerang, Banten. Conducted from September to October 2023, this research aims to test the proposed hypothesis through statistical analysis by using a quantitative approach. Data were collected using research instruments, and analysis was carried out to objectively assess the relationship between workforce diversity and job satisfaction. Non-probability sampling was conducted to ensure practical access to respondents. The sample size determined was 150 employees in South Tangerang. These findings reveal a positive and significant influence of workforce diversity on job satisfaction, challenging common assumptions regarding the acceptance of differences. Contrary to popular belief, research results show a high level of acceptance of workforce diversity, thereby contributing to increased job satisfaction among employees. This study offers a new perspective on the impact of workforce diversity on job satisfaction, and emphasizes its relevance in the specific context of South Tangerang.